INTEGRATION OF PESTLE AND TOWS METHODS FOR STRATEGY MANAGEMENT OF THE PALM PALM MANUFACTURING INDUSTRY (CASE STUDY: PT. JOHAN SANTOSA) - Bamatraf, Lutfia; Fasih, Ahmad; Vangesti, Wanvia; Hariastuti, Ni Luh Putu (Universitas Nusantara PGRI Kediri, 2024)
This research aims to analyze the application of the integration of the PESTLE and TOWS methods in the strategic management of PT. Johan Sentosa, a palm oil manufacturing company in Kampar Regency, Indonesia. Using a qualitative descriptive approach, this research combines primary data from semi-structured interviews with management and secondary data from company documents and industry publications. The research methodology includes data collection through interviews, documentation studies, and direct observation. Data analysis was carried out using data reduction techniques, data presentation, PESTLE analysis, TOWS analysis, and integration of analysis results. The research results show that PESTLE factors have a significant influence on the palm oil manufacturing industry, with EFAS analysis producing a total score of 5.0 (opportunities 2.8, threats 2.2). TOWS analysis identifies PT's strengths and weaknesses. Johan Sentosa, with IFAS analysis produced a total score of 3.4 (strengths 1.85, weaknesses 1.55). The integration of both methods results in a strategy that capitalizes on a company's strengths and market opportunities, such as ongoing product development and technology investments, while addressing weaknesses and threats through improved operational efficiency and environmental risk management. This research provides a comprehensive framework for strategic analysis in the palm oil manufacturing industry, with practical implications for PT. Johan Sentosa in increasing the competitiveness and sustainability of its business.Keywords: Pestle, Tows, Strategic Management, PT. Johan Sentosa